ENABLE (Exportable Notation and Bookmark List Engine): an Interface to Manage Tumor Measurement Data from PACS to Cancer Databases. - Goyal, Nikhil; Bagheri, Mohammad; Machado, Laura; Folio, Les; Apolo, Andrea; Berman, Eliana; Levine, Jason; Glod, John; Kaplan, Rosandra (Journal of Digital Imaging, 2017)
Oncologists evaluate therapeutic response in cancer trials based on tumor quantification following selected 'target' lesions over time. At our cancer center, a majority of oncologists use Response Evaluation Criteria in Solid Tumors (RECIST) v1.1 quantifying tumor progression based on lesion measurements on imaging. Currently, our oncologists handwrite tumor measurements, followed by multiple manual data transfers; however, our Picture Archiving Communication System (PACS) (Carestream Health, Rochester, NY) has the ability to export tumor measurements, making it possible to manage tumor metadata digitally. We developed an interface, 'Exportable Notation and Bookmark List Engine' (ENABLE), which produces prepopulated RECIST v1.1 worksheets and compiles cohort data and data models from PACS measurement data, thus eliminating handwriting and manual data transcription. We compared RECIST v1.1 data from eight patients (16 computed tomography exams) enrolled in an IRB-approved therapeutic trial with ENABLE outputs: 10 data fields with a total of 194 data points. All data in ENABLE's output matched with the existing data. Seven staff were taught how to use the interface with a 5-min explanatory instructional video. All were able to use ENABLE successfully without additional guidance. We additionally assessed 42 metastatic genitourinary cancer patients with available RECIST data within PACS to produce a best response waterfall plot. ENABLE manages tumor measurements and associated metadata exported from PACS, producing forms and data models compatible with cancer databases, obviating handwriting and the manual re-entry of data. Automation should reduce transcription errors and improve efficiency and the auditing process.